ARCHITECTONICS OF AMERICAN COURTROOM DISCOURSE: AN IMPLICIT WAY OF CONTENT MANAGEMENT - Margaryta O. Zaitseva; Stina Ericsson (Alfred Nobel University Journal of Philology)
The article examines the specificity of courtroom discourse as a communicative integrity, which is manifested in the comprehensive coherence of its information components. The proposed paper signifi- cantly contributes to the existing studies on the linguistics of courtroom discourse, focusing on the study of its architectonics, a problem that is currently on the periphery of researchers’ scientific interests. The ne- cessity (relevance) of studying courtroom discourse as a comprehensive information cluster, including in- teraction and subordination of its components, is explained by the need to identify the factors ensuring the effectiveness of the communication process. All this determines the novelty of the research. The aim of our study is to define the nature of courtroom discourse and its architectonics from the point of the information it contains, its arrangement, and its impact on the audience. To achieve this aim, both general scientific methods (analysis, synthesis, systematisation, classification, induction, deduction) and strictly linguistic methods (random sampling and observation, lexical-semantic and contextual analysis, interpretation of dictionary definitions) were used. In addition, the method of sociolinguistic analysis of the corpus was employed to study the interdependence between language and society. The aim has led to the following objectives: to establish kinds of information the courtroom discourse is based on; to determine the way of how it is delivered and organised to strongly impact the recipients; to justify the notion of architectonics in using it to courtroom discourse. The corpus material was the texts of the opening and closing speeches of prosecutors and defense lawyers at the two high-profile trials of 1999 – 2000 and 2021 (the Amadou Diallo Trial (1999–2000); the George Floyd Murder (Chauvin) Trial (2021). The findings of the study were as follows: It has been established that communication in court, in terms of its focus on the effective exchange of various kinds of information, affects the following: a) the rational perception (semantic information, impact on the mind); b) the emotional perception (aesthetic information, impact on emotions); c) the irratio- nal perception (synectic information, impact on the unconscious) that form an information cluster. It has been shown for the first time that the effectiveness of the communication process in court is determined by the extent of impact or depth of penetration of resources of each kind of information. The concept of architectonics is clarified as a certain, a coordinated and coherent arrangement of blocks of discourse, not reducible to the sum of these blocks, determined by the overall goal of the author in relation to the delivery and impact of information. It is emphasised that the architectonics of discourse affects and implicitly manages the process of audience’s perception of its content. The research also first establishes that the architectonics of the prosecution discourse is constructed through progressive disclosure. Conversely, the discursive space of the defense is organised through the vi- sualisation of a narrative, with the main theme, idea, or concept at its center. The topics that provide expla- nation are arranged around it. Such construct of architectonics is based on the principle of mindmapping. Both constructs provide legal professionals with almost unlimited scope of the creativity to set up the nec- essary chains of association. It is necessary to mention that personal attitudes should be introduced into the architectonics of courtroom discourse as well as a myth created. This also determines, among other things, the success of courtroom discourse. The classification of types of transgression based on their impact on the recipients has been supple- mented, namely, constructive and disruptive ones. The study shows promise as it would be intriguing to explore this issue from the perspective of the evolution of the architectonics of courtroom discourse.